An improved multistage switched inductor boost converter (improved M-SIBC) for renewable energy applications: a key to enhance conversion ratio - Bhaskar, Mahajan Sagar; Padmanaban, Sanjeevikumar; Blaabjerg, Frede; Wheeler, Patrick (2018)
In this article, an improved Multistage Switched Inductor (M-SI) based power converter or Improved Multistage Switched Inductor Boost Converter (Improved M-SIBC) is proposed for renewable applications which provides a key to enhance voltage conversion ratio. In last decades, Switched Inductor (SI) and M-SI are the popular network/technique employed in DC-DC converter to achieve high voltage conversion ratio. An improved SI and M-SI network/technique is proposed to enhance the existing the voltage conversion capabilities of SI and M-SI by replacing central uncontrolled switches by polarized capacitor. The anticipated power converter configuration combines the feature of conventional boost converter and improved M-SI. The voltage conversion a capability is depends on the number of stages of M-SI and ON time of control switch. The operation modes and characteristics of proposed converter with steady state mathematical analysis for N-stages are discussed in detail. Moreover, the proposed converter compared with existing converter in terms of voltage conversion ratio and the detail of number of components is also provided. Matrix Laboratory R2016a simulation results of 100W proposed improved M-SIBC with considering three stages are provided and the results always shows a good agreement with theoretical analysis and also validates the improved M-SI network concept.